The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/nu15071702
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol as a Modulator of the Development of Alcohol Tolerance in Rats

Abstract: The study aimed to explore in vivo the influence of cannabidiol (CBD) on the development of alcohol tolerance in rats. Rats were treated with ethanol (3.0 g/kg, i.p.) and CBD (20 mg/kg, p.o.) for nine successive days, and rectal body temperature, sedation (sleeping time), and blood alcohol concentration (BAC) were measured. In the prefrontal cortex, hippocampus, and striatum, the cannabinoid (CB1R and CB2R) and dopaminergic (DRD1, DRD2, DRD4, DRD5) receptors’ mRNA level changes were analyzed using the quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 96 publications
(148 reference statements)
1
1
0
Order By: Relevance
“…According to the preliminary data presented in Figure S1 , the administration of 20 mg/kg CBD-LNP had no significant effect on the locomotor activities of normal rats in the open field test (OFT), while concurrently reducing anxiety levels as observed in the elevated-plus maze. This observation is consistent with previous studies conducted by Costa et al, 2007 and Szulc et al, 2013, which demonstrated the potential of CBD in alleviating inflammatory and neuropathic pain, as well as mitigating alcohol tolerance in rats [ 24 , 25 ]. Therefore, considering the positive outcomes reported in these studies, it was decided to orally administer 20 mg/kg CBD-LNP to DP rats.…”
Section: Methodssupporting
confidence: 93%
“…According to the preliminary data presented in Figure S1 , the administration of 20 mg/kg CBD-LNP had no significant effect on the locomotor activities of normal rats in the open field test (OFT), while concurrently reducing anxiety levels as observed in the elevated-plus maze. This observation is consistent with previous studies conducted by Costa et al, 2007 and Szulc et al, 2013, which demonstrated the potential of CBD in alleviating inflammatory and neuropathic pain, as well as mitigating alcohol tolerance in rats [ 24 , 25 ]. Therefore, considering the positive outcomes reported in these studies, it was decided to orally administer 20 mg/kg CBD-LNP to DP rats.…”
Section: Methodssupporting
confidence: 93%
“…On the molecular level, the most expressed effect of the ethanol-CBD intervention was observed in the striatum, where CBD inverted the ethanol-induced down-regulation of CB2R gene transcription. The opposite effect was observed for the mRNA of CB1 and dopaminergic receptors (DRD1, DRD2) [78].…”
mentioning
confidence: 81%